Bullous and haemorrhagic lichen sclerosus with scalp involvement. - Marren, P; De Berker, D; Millard, P; Wojnarowska, F (1992)
We describe a patient who developed a generalized blistering eruption due to lichen sclerosus and who was observed to have scalp involvement. Both are unusual manifestations of this disease which merit consideration. Lichen sclerosus is an uncommon disease that most frequently affects the external genitalia of perimenopausal women. The aetiology is unknown. Approximately 20% of affected patients have extragenital lesions that present as small, ivory, shiny round macules or papules that later become atrophic; extragenital lesions are generally asymptomatic. Bullous and haemorrhagic forms may occur but these are generally localized and reports of extensive or generalized involvement are rare. We describe an elderly woman with generalized bullous lichen sclerosus. As an incidental finding, she was observed to have lichen sclerosus affecting her scalp. This has rarely been described and it would appear that she is the third reported case of scalp involvement.